Analisis Kepuasan Konsumen Berdasarkan Service Quality Menggunakan Metode Customer Satisfaction Index (CSI) dan Importance Performance Analiysis (IPA) - Sari, Fadia Paloma; Rosiana, Intan Maharani; Merlin, Kianeta; Purwanto, Qurrota A'yun; Febriana, Latifah Helsa; Pangestuty, Afifah (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
Tight competition in the culinary business makes many entrepreneurs compete to provide the best service, and the customers feel satisfied with their products. Jujugan Cafe is one of the culinary businesses in the UIN Raden Mas Surakarta campus environment. However, Jujugan Cafe has received several complaints from customers regarding service quality. To understand and improve the customer experience, researchers conduct regular surveys or assessments to get customer feedback about the quality of service. This research focuses on measuring and analyzing the level of service quality of Jujugan Cafe consumer satisfaction. In this research, the SERVQUAL method was used to identify aspects that affect the quality of Jujugan Cafe's service; the CSI application is useful in measuring consumer satisfaction, while IPA is used in measuring the level of conformity between performance and interest factors. This research showed the percentage of the CSI method of 81.73%, indicating that customers are at a very satisfied level. Based on the IPA analysis, the attribute that is the top priority for improvement is that employees immediately serve consumers when they visit. For this reason, the recommended solution is to improve service quality. In addition, Jujugan cafe also needs to pay attention to the low satisfaction level aspects, which are of high importance.